Intravenous administration of cardiac progenitor cell-derived exosomes protects against doxorubicin/trastuzumab-induced cardiac toxicity. Issue 2 (30th April 2019) - Milano, Giuseppina; Biemmi, Vanessa; Lazzarini, Edoardo; Balbi, Carolina; Ciullo, Alessandra; Bolis, Sara; Ameri, Pietro; Di Silvestre, Dario; Mauri, Pierluigi; Barile, Lucio; Vassalli, Giuseppe
Abstract: Aims: Combined administration of anthracyclines (e.g. doxorubicin; Dox) and trastuzumab (Trz), a humanized anti-human epidermal growth factor receptor 2 (HER2; ErbB2), is an effective treatment for HER2-positive breast cancer. However, both agents are associated with cardiac toxicity. Human cardiac-resident mesenchymal progenitor cells (CPCs) secrete extracellular vesicles including nanosized exosomes which protect against myocardial ischaemia. Here, we investigated the effects of these exosomes using a novel model of Dox/Trz-mediated cardiotoxicity. Methods and results: CPCs were derived from cardiac atrial appendage specimens from patients who underwent heart surgery for heart valve disease and/or ischaemic heart disease, and exosomes were purified from CPC conditioned media. Proteomics analyses revealed that CPC exosomes contained multiple proteins involved in redox processes. Dox/Trz induced a significant increase in reactive oxygen species (ROS) in rat cardiomyocytes, which was prevented by CPC exosomes. In vivo, rats received six doses of Dox (Days 1–11), followed by six doses of Trz (Days 19–28). Three doses of either exosomes or exosome suspension vehicle were injected intravenously on Days 5, 11, and 19 in the treatment and control groups, respectively. Dox/Trz induced myocardial fibrosis, CD68 + inflammatory cell infiltrates, inducible nitric oxide synthase expression, and left ventricular dysfunction. CPC exosomes prevented these effects. These vesicles were highly enriched in miR-146a-5p compared with human dermal fibroblast exosomes. Dox upregulated Traf6 and Mpo, two known miR-146a-5p target genes (which encode signalling mediators of inflammatory and cell death axes) in myocytes. CPC exosomes suppressed miR-146a-5p target genes Traf6, Smad4, Irak1, Nox4, and Mpo in Dox-treated cells. Specific silencing of miR-146a-5p abrogated exosome-mediated suppression of those genes leading to an increase in Dox-induced cell death. Conclusions: Human CPC exosomes attenuate Dox-/Trz-induced oxidative stress in cardiomyocytes. Systemic administration of these vesicles prevents Dox/Trz cardiotoxicity in vivo . miR-146a-5p mediates some of the benefits of exosomes in this setting.